Propuesta urbano-arquitectónica de una fábrica de ladrillos como centro de gestión en la industria ladrillera del Cantón Chambo - Alvarez Bayas, Vanessa Gabriela (2025)
This research proposes an urban architectural design for a sustainable brick factory serving as a management center for the brick industry in Chambo Canton, Ecuador. It begins with a comprehensive diagnosis that reveals the disorganized spatial distribution of brick kilns, negative environmental impacts, poor working conditions, and a lack of technological advancements in employment within the artisanal sector. By studying contemporary architectural works that prominently and structurally incorporate bricks, a set of design criteria is formulated that combines environmental sustainability, cultural identity, and energy efficiency. The project proposes territorial and community management, as well as technical training spaces, to enhance production conditions and environmental control, consolidate an associative model of collaboration between producers, reduce environmental impact, and improve productivity. The proposed architectural design incorporates clean technologies, such as high-efficiency ovens, and applies principles of modern industrial architecture to enhance functionality and minimize ecological impact. The intention is that the offer serves as a model to aid in the regeneration of the urban ecosystem and the sustainable development of traditional productive activities. This work demonstrates that architecture can positively impact precarious economies through transformative interventions, such as the integration of balance it brings to the unstable socio-economic system, substantive solidarity, and ecological sustainability.